FUN LEARNING STRATEGY TO ENHANCE ENGLISH LITERACY - Zahrina; Cut Keumalawati; Qadrun Nida; Syifa Mardatillah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2023)
This study aims to determine how fun learning can enhance English Literacy. The subjects of the research were 35 children of Sentosa Village, they were at the level elementary school. This research was descriptive research. The instruments used were observation sheets and interview guides. The result of the research was divided in two sections. First based on observation and second was based on interview data. The observation result indicated that the children had positive responses on the implementation of fun learning strategy to learn English literacy. Furthermore, through interview the students clarified that they had been motivated and they felt a lot of enjoyable learning by the applied method.